A selective fluorescent probe for gadoliniumIII in water based on a PdII-preorganized chromone-receptor. Issue 42 (19th October 2021) - Paderni, Daniele; Giorgi, Luca; Macedi, Eleonora; Formica, Mauro; Paoli, Paola; Rossi, Patrizia; Fusi, Vieri
Abstract : A preorganized Pd II complex able to sense Gd III ions in real aqueous samples via an OFF–ON fluorescence signal. Abstract : The synthesis, solution studies, photochemical properties and the X-ray structure of a chromone based fluorescent Pd II complex are reported. The ligand contains two chromone units linked as side arms to an ethylenediamine moiety; in the Pd II complex the metal ion preorganizes the two hydroxychromone units forming a rigid structure with a negatively charged pocket formed by four oxygen atoms that is able to interact with hard metal cations, such as ions, giving rise to stable bimetallic complexes. Upon interaction with La III and Gd III, in particular, the emission intensity at 423 nm increases by a factor of 2 and 8, respectively, while the other rare earth ions quench the fluorescence. Spectrofluorimetric studies on real matrices showed the possibility to use this system as a selective fluorescence probe to detect and trace the presence of Gadolinium in environmental water acting as an OFF–ON chemosensor, with a LOD of 0.4 ppm and a LOQ of 1.2 ppm.